2009
DOI: 10.1364/oe.17.021497
|View full text |Cite
|
Sign up to set email alerts
|

Modulation instability, Akhmediev Breathers and continuous wave supercontinuum generation

Abstract: Numerical simulations of the onset phase of continuous wave supercontinuum generation from modulation instability show that the structure of the field as it develops can be interpreted in terms of the properties of Akhmediev Breathers. Numerical and analytical results are compared with experimental measurements of spectral broadening in photonic crystal fiber using nanosecond pulses.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
353
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 490 publications
(371 citation statements)
references
References 38 publications
17
353
1
Order By: Relevance
“…In the following, we focus on the particular family of AB solutions [2], c AB ¼ c SFB ð0 < a < 1=2Þ, which describes the nonlinear compression of a modulated continuous wave field into a periodic train of ultrashort pulses with temporal period T ¼ 2 =!. c AB is valid over the range of modulation frequencies that experience MI gain (0 < !…”
Section: Analytical and Numerical Predictionsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the following, we focus on the particular family of AB solutions [2], c AB ¼ c SFB ð0 < a < 1=2Þ, which describes the nonlinear compression of a modulated continuous wave field into a periodic train of ultrashort pulses with temporal period T ¼ 2 =!. c AB is valid over the range of modulation frequencies that experience MI gain (0 < !…”
Section: Analytical and Numerical Predictionsmentioning
confidence: 99%
“…However, certain initial conditions used in practice are known to yield periodic evolution as a function of propagation [2], but even in this case, the first growth-return cycles remain well-described individually by the analytic AB solution. Figures 1(c) and 1(d) illustrate such a biperiodic behavior through the evolution of the following periodic perturbation c IN ¼ ½1 þ mod cosð!…”
Section: Analytical and Numerical Predictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, most of spontaneous pattern formations and localized structures induced by MI could now be described by using such generalized solutions, even when the background itself is localized in time (i.e., a laser pulse). It was already shown that breather dynamics with pulsed excitation can be interpreted in terms of local breather states at different points on the pulse envelope [36,37]. Superregular breathers give an enlarged and generalized picture of the collision features with respect to recent numerical and experimental studies of breather structures and their interactions in optics or hydrodynamics [29][30][31]38].…”
Section: Introductionmentioning
confidence: 99%